Potret Pola Pendidikan Agama Islam Keluarga Pekerja Perkebunan Teh Desa Tangsi Baru Kabawetan - Leni Marlina; Fakruddin Fakruddin; Muksal Mina Putra (Institut Agama Islam Negeri Bengkulu, 2020)
Abstract: The Portrayal Of Islamic Religious Education Patterns Of The Workers’ Family At The Tea Plantation In Tangsi Baru Village Kabawetan The family is a small part of society that consists of a father, mother (parents), and children. Parents are the first and foremost educators for every child. When parents have other professions outside the home, they definitely still have to prioritize religious education for their children even in the early years. In this regard, how are the patterns of familial education in Tangsi Baru Village, Kabawetan, Kepahiang Regency, in the midst of families as the tea laborers? To answer the foregoing question, this study used a qualitative approach. The data collection techniques were interviews and observations, and the data were then analyzed in a qualitative way. The conclusion is showed that the most widely applied pattern of Islamic education in the family was a democratic pattern, with the reason in order that their children are not circumscribed by the parents’ rules, in the meantime, their control is very limited because of being the plantation workersAbstrak : Potret Pola Pendidikan Agama Islam Keluarga Pekerja Perkebunan Teh Desa Tangsi Baru Kabawetan Keluarga adalah bagian kecil dari masyarakat yang terdiri dari ayah, ibu (orang tua) dan anak. Orang tua merupakan pendidik pertama dan utama bagi setiap anak. Ketika orang tua memiliki profesi yang lain selain di rumah, tentu tetap harus mengedepankan pendidikan agama pada anak mereka bahkan sejak usia kanak-kanak. Bagaimanakah dengan pola pendidikan dalam keluarga di Desa Tangsi Baru Kabawetan Kabupaten Kepahiang, di tengah keluarga yang notabene berprofesi sebagai pekerja perkebunan Teh?. Penelitian ini menggunakan pendekatan kualitatif. Alat pengumpul data yang digunakan adalah wawancara dan observasi selanjutnya dianalisis dengan pendekatan kualitatif pula. Kesimpulan hasil penelitian ini menunjukkan bahwa pola pendidikan Agama Islam dalam keluarga yang paling banyak diterapkan adalah pola demokratis, dengan alasan agar anak mereka tidak terkungkung dengan aturan dari orang tua sementara pengawasan mereka sangat terbatas karena kesibukan sebagai pekerja perkebunan